The relationship between problematic internet use and parenting models in the junior high school students in the pandemic era - Imam Ariffudin; Ajeng Intan Nur Rahmawati (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2022)
Purpose: This study aims to analyze the relationship and the influence of parental parenting on students' PIU levels.Method: Correlational research with an explanatory design was chosen to answer the formulation of the research problem. A total of 121 junior high schools (SMP) students in Malang City were respondents to the study using random sampling. The research data was collected using two instruments, namely generalized problematic Internet Use Scale 2 (GPIUS2) and the Parenting Questionnaire in Alabama. The collected data were analyzed using multiple regression.Result: The results showed that inconsistent discipline, poor monitoring/supervision, and corporal punishment are variables that predict an increase in student PIU. Thus, it can be concluded that parental parenting is related and has an effect on the high and low levels of PIU.Implication: Therefore, parents need to adjust parenting by helping students in improving self-control during a pandemic that uses more internet access.Originality: This research is a study that focuses on analyzing problems that arise in the pandemic era related to problematic internet use (PIU) and parental parenting models.***Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan dan pengaruh Problematic Internet Use (PIU) terhadap pola asuh orang tua pada siswa SMA Kota Malang.Metode: Correlational research with explanatory design was chosen to answer the formulation of the research problem. A total of 121 junior high school (SMP) students in Malang City were respondents to the study using random sampling. The research data was collected using two instruments, namely generalized problematic Internet Use Scale 2 (GPIUS2) and Parenting Questionairre Alabama. The collected data were analyzed using multiple regression analysis.Hasil: Hasil penelitian menunjukkan bahwa model pola asuh memiliki hubungan dan berpengaruh terhadap tingkat penggunaan internet bermasalah. Inconsistent discipline, poor monitoring/supervision dan corporal punishment merupakan variable yang dapat memprediksi peningkatan PIU siswa.Implikasi: Kajian ini berperan penting bagi instansi, guru, dan orang tua untuk menumbuhkan self-control sebagai upaya dalam menentukan pola asuh yang tepat kepada peserta didik ketika menggunakan internet.Orisinalitas: Penelitian ini merupakan kajian yang menitikberatkan pada permasalahan Problematic Internet Use (PIU) dan model pola asuh orang tua selama pandemi di Kota Malang.